2014
DOI: 10.1530/rep-13-0563
|View full text |Cite
|
Sign up to set email alerts
|

2-Arachidonoylglycerol effects in cytotrophoblasts: metabolic enzymes expression and apoptosis in BeWo cells

Abstract: The major endocannabinoid (eCB) 2-arachidonoylglycerol (2-AG) is a member of the endocannabinoid system (ECS) that participates in cell proliferation and apoptosis, important events for the homoeostasis of biological systems. The formation of placenta is one of the most important stages of pregnancy and its development requires highly regulated proliferation, differentiation and apoptosis of trophoblasts. Anomalies in these processes are associated with gestational pathologies. In this work, we aimed to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…Conversely, stimulation of the ECS has also been demonstrated to induce the production of ROS in certain cell types [ 69 71 ]. For example, 2-AG stimulation has been shown to promote an increase in cellular ROS in BeWo trophoblasts [ 71 ].…”
Section: Endocannabinoid System-mediated Regulation Of Reactive Oxygementioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, stimulation of the ECS has also been demonstrated to induce the production of ROS in certain cell types [ 69 71 ]. For example, 2-AG stimulation has been shown to promote an increase in cellular ROS in BeWo trophoblasts [ 71 ].…”
Section: Endocannabinoid System-mediated Regulation Of Reactive Oxygementioning
confidence: 99%
“…Conversely, stimulation of the ECS has also been demonstrated to induce the production of ROS in certain cell types [ 69 71 ]. For example, 2-AG stimulation has been shown to promote an increase in cellular ROS in BeWo trophoblasts [ 71 ]. Moreover, increased ROS and concomitant TNF- α cytokine production have been reported in human macrophages following CB1R activation, with both responses being attenuated by pharmacological inhibition of CB1R [ 69 ].…”
Section: Endocannabinoid System-mediated Regulation Of Reactive Oxygementioning
confidence: 99%
“…We previously described that 2-AG interferes with cytotrophoblast syncytialization through a CB receptor-dependent mechanism ( Costa et al 2015 c ). Moreover, in BeWo cells, we found that 2-AG induces trophoblast apoptosis, through mitochondrial membrane potential loss and increase in ROS generation and caspase -3/-7 and -9 activities, suggesting the activation of the mitochondrial pathway ( Costa et al 2014 a ). The endocannabinoid 2-AG is therefore implicated in normal trophoblast turnover.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, we previously demonstrated that AEA and 2-AG impair the synthesis of proteins and hormones by the human syncytiotrophoblast ( Costa et al 2015 a , 2016 ). In addition, AEA and 2-AG are able to modulate trophoblast apoptosis by inducing caspase activation and reactive oxygen species (ROS) generation ( Costa et al 2014 a , b , 2015 b ).…”
Section: Introductionmentioning
confidence: 99%
“…The functional activity of the decidual cells was evaluated by measuring the alkaline phosphatase (ALP) activity as previously described (Costa et al, 2014). Briefly, cells from 24-well plates were rinsed with buffer and then incubated at 37°C for 1 h with the pALP substrate p-nitrophenilphosphate, 2.5 mM (Sigma Chemical Co, St. Louis, MO, USA), in the presence of 100 mM MgCl2 (Sigma Chemical Co, St. Louis, MO, USA).…”
Section: Decidual Alkaline Phosphatase Activity Assaymentioning
confidence: 99%